Superior somatic pain relief and improved visceral pain control is achieved using pre-emptive analgesia for laparoscopic cholecystectomy: A randomized controlled trial - Koh, P.S.; Cha, K.H.; Lucy, C.; Rampal, S.; Yoong, B.K. (University of Malaya Medical Centre, 2012)
BACKGROUND: Laparoscopic cholecystectomy, although is less invasive than open surgery, is not completely pain free. The use of local anaesthesia to relieve pain following this procedure is a common practice. However, it remains debatable whether a pre- or post-operative drug administration is more effective. Here, we investigated the role of preemptive local anaesthetic infiltration given pre- or post-incisional, in relieving the pain during laparoscopic surgery. METHODOLOGY: A randomized controlled trial was conducted with 96 patients receiving 0.5% Bupivacaine 100mg. Group A (n=48) received post-incisional skin infiltration whilst Group B (n=48) received pre-incisional infiltration. Incisional (somatic) and intra-abdominal (visceral) pain was assessed using Visual Analog Scale (VAS) at day 0, day 1 and day 7 post-operative days. RESULT: Baseline characteristics between the two groups were similar. Incisional pain was lower in Group B as compared to Group A at day 0 (P=0.03) and day 1 (P<0.01). Intra-abdominal pain was also lower in Group B at day 0 and day 1 (P=0.04). VAS score was similar at day 7 although analgesia requirement is higher in Group A (P>0.05). CONCLUSION: Administration of pre-incisional local anaesthesia offers better pre-emptive pain relief measure than post-incisional administration by reducing somatic and visceral pain in laparoscopic gall bladder surgery.